Engineering problem solving a classical perspective - Shaw, Milton C. 1915-2006 (Noyes Pub./William Andrew Pub., 2001)
" ... revisits the development of engineering as a problem-solving profession, beginning from its origins in the classic text: Dialogues Concerning Two New Sciences, by Galileo Galilei, originally published in 1638 ... discussions of passages from the Galileo text emphasize the roles played by experimentation and dialog in engineering analysis and creativity; that is, the 'mind' set of engineering. Throughout this book, the often-circuitous route taken in the development of new ideas is illustrated"--Page 4 of cover.
Companion to electronic version of: Dialogues concerning two new sciences / Galileo Galilei (Norwich, N.Y. : William Andrew, 2001).
Chiefly engineering problems; answers given on p. 453-466.
Includes indexes.
Keywords: Galilei, Galileo, -- 1564-1642. -- Discorsi e dimostrazioni matematiche. -- English.; Discorsi e dimostrazioni matematiche (Galilei, Galileo); Engineering mathematics.; Engineering -- History.; elektronické knihy; electronic books